2008
DOI: 10.1097/qai.0b013e3181648e16
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypercholesterolemia Incidence With Antiretroviral Treatment, Including Protease Inhibitors, Among Perinatally HIV-Infected Children

Abstract: PIs were significant risk factors for hypercholesterolemia. Higher viral load was protective and may reflect nonadherence. Further follow-up is critical to evaluate long-term consequences of chronic PI exposure and hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 37 publications
7
54
0
3
Order By: Relevance
“…A alta prevalência de dislipidemia (88,3%) observada no nosso estudo está acima da encontrada na literatura 8,18,19 . Isto pode ter ocorrido devido a que as referências utilizadas para a análise dos lipídios séricos apresentavam um ponto de corte mais elevado.…”
Section: Discussionunclassified
“…A alta prevalência de dislipidemia (88,3%) observada no nosso estudo está acima da encontrada na literatura 8,18,19 . Isto pode ter ocorrido devido a que as referências utilizadas para a análise dos lipídios séricos apresentavam um ponto de corte mais elevado.…”
Section: Discussionunclassified
“…17 The high prevalence of dyslipidemia (88.3%) found in the present study is above the rate found in the literature. 8,18,19 This may have been caused by the fact that the references used for the analysis of serum lipids had a higher cutoff point. Nevertheless, this prevalence of dyslipidemia may also be a consequence of HIV infection itself.…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se de um perfil reconhecidamente aterogénico e que está relacionado sobretudo com o uso de inibidores da protease. [35][36][37][38] Investigação laboratorial demonstrou que o efeito hiperlipidemiante destes fármacos é provavelmente devido à inibição da atividade de certas proteínas-chave do metabolismo lipídico, como por exemplo o recetor de LDL (LDLR) e a proteína relacionada com LDLR (LRP). Essa inibição diminuiria a capacidade dos hepató-citos e das células endoteliais de removerem da circulação os quilomicrons (ricos em triglicerídeos) e as partículas LDL, aumentando assim o seu teor plasmático.…”
Section: Estado Pró-ateroscleróticounclassified